An Application for Alumni of Soegijapranata Catholic University - Hanna Mulianawati; Ridwan Sanjaya; FX Hendra Prasetya (SISFORMA, 2019)
Sometimes it’s hard for the university to get the information about their own alumni after the graduation ceremony. The situation of the alumni is also the same. They felt difficult to reach their university after they got a job. Some services and documents are still needed by the alumni for any reason. In fact, people nowadays live with their smartphone really closely. The smartphone could help people to get information and services while keeping them close to their community. The mobile application should be built to connect alumni and university through a smartphone via information sharing about job vacancy and providing some university’s services. Some methods are used in the process of mobile application development, such as designing the application, programming, testing, and launching. Interview and survey are done to know the responses in using the application. The conclusions of the research are the application could help the alumni to get information and services, the university is able to gain the updated data of their alumni, and make both of them closer.